Occurrence of mental health symptoms and disorders in current and former elite athletes: a systematic review and meta-analysis - Gouttebarge, V.; Castaldelli-Maia, J. M.; Gorczynski, P.; Hainline, B.; Hitchcock, M. E.; Kerkhoffs, G. M.; Rice, S. M.; Reardon, C. L. (British Journal of Sports Medicine, 2019)
Objectives: To present an overview of the existing epidemiological evidence regarding the occurrence of mental health symptoms and disorders among current and former elite athletes.